(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article examines the phenomenon of attention fragmentation in media-rich English as a Foreign Language (EFL) classrooms within the context of Uzbekistan’s digitalized educational environment. The increasing use of smartphones, online platforms, multimedia technologies, and digital applications in language education has transformed classroom interaction and learning strategies. At the same time, the overuse of digital tools may divide learners’ attention and negatively influence concentration, memory retention, and language acquisition outcomes. The research analyzes how media-rich environments affect vocabulary learning, listening comprehension, reading performance, classroom participation, and academic motivation among EFL students in Uzbekistan. The article employs qualitative and analytical methods based on existing educational practices, teacher observations, and theoretical perspectives related to digital pedagogy. The findings indicate that while digital technologies improve access to authentic English-language resources and increase learner engagement, uncontrolled multitasking and excessive media exposure reduce deep learning processes and create cognitive overload. The study concludes that balanced digital integration, pedagogical discipline, and learner-centered classroom management are necessary to maximize the advantages of technology while minimizing attention fragmentation in EFL instruction [1; 2].